Current problems of organization of social work persons who have been prosecuted - Svetlana Denizhna; Anna Sinotova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
In this article the problems of social work with persons who have served their criminal sentences in prison and were brought to justice. Characteristic problems of social work persons were brought to criminal responsibility. Provided legal and methodical providing social support to persons who have been brought to criminal responsibility.